Evaluasi Model CIPP pada Program Ekstrakurikuler Kewirausahaan di SMA - Laily Mustainah; Muhamad Sholehi; Mufarrihul Hazin; Amrozi Khamidi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study is a literature review that aims to evaluate the entrepreneurship extracurricular program at the high school level using the Systematic Literature Review (SLR) approach that follows the PRISMA guidelines. This method is used to identify, evaluate, and synthesize various relevant studies from reputable scientific sources through databases such as Google Scholar and Semantic Scholar. The evaluation was conducted using the CIPP (Context, Input, Process, Product) model to provide a comprehensive picture of the program's implementation. The results of the study indicate that in the context component, the entrepreneurship program aims to instill entrepreneurial character from an early age and reduce unemployment rates. In the input component, the main obstacle lies in the limited facilities and infrastructure even though the supervising teachers have met the qualifications. The process component shows that the implementation of activities is going according to plan, but increasing student self-confidence still needs to be strengthened. Meanwhile, in the product component, the program has a positive impact on the development of students' entrepreneurial skills, but its effectiveness is greatly influenced by the quality of implementation in the three previous components. These findings are expected to be the basis for developing a more effective and sustainable entrepreneurship program in schools. Keywords: Systematic Literature Review, Entrepreneurship Extracurricular, PRISMA